LASER DECORATIVE PROCESSING OF COTTON AND TEXTILE CLUSTER EMPLOYEES SPECIAL CLOTHING - Khujayeva Malika Ergash kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation.The textile industry has witnessed significant advancements in recent years, especially in the realm of decorative processing for special clothing worn by employees in cotton and textile clusters. Laser technology has emerged as a game-changer in this domain, offering precision, versatility, and efficiency in creating intricate designs on textile materials. This article explores the methods, results, and implications of laser decorative processing for special employee clothing within cotton and textile clusters. We present the benefits and challenges associated with this innovative technique and offer insights into its future prospects.